Translation Studies In The Arab World Trends & Impacts: A Bibliometric Study Of Published Articles Funded By Arabic Observatory Of Translation/ دراسات الترجمة في الوطن العربي الاتجاهات والتأثير: دراسة ببيليومترية للأبحاث الممولة بواسطة المرصد العربي للترجمة - Jibreel, Ibrahim (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
This bibliometric study aimed to investigate the relationship between trends and impact of translation studies (TS) in the Arab World, exploring the correlation between an article’s trend and citation as well as some other factors, namely year of publication, authorship (sole author/coauthors), scope/s(uni-/bi-), source of citation, and journal indexing. In addition, it attempted to map the contribution to the TS movement in the Arab World regarding the author’s nationality and university affiliation. The bibliometric analysis depended on the Arabic Observatory of Translation (AOT) beta-website’s corpus to collect data from 125 articles of two translation grant sessions (2022 & 2023). The titles of articles were thematically analyzed and quantified in frequencies and percentages, and the Citation Analysis (CA) helped to record the research’s impact utilizing Google Scholar. The other influential potential factors were controlled for internal validity, and the two-rater method was utilized for reliability. Pearson Correlation, Partial Correlation Analysis, and Multiple Linear Regression were used in the analysis regarding correlations. Translation technology, literary translation, and audio-visual were the most frequent trends among all the trends funded by the AOT. However, the correlation between research trend and impact is weak, negative, and insignificant (r=-.067, p=0.476). The results also showed that interdisciplinary scopes have a positive correlation and significant effect on articles’ citations (B = 4.41, β = 0.29, p < .001), while journal indexing has a negative correlation and significant impact (B = -1.22, β = -0.34, p < .001). Factors like authorship, research trend, citation source, and publication year insignificantly influenced articles’ citation (p >.05). Mapping TS movement contribution, by nationality, Saudi researchers ranked first, followed by Yemeni, Jordanian, and Egyptian, respectively. King Saud University made a significant contribution among universities, followed by King Abdulaziz University, Applied Science Private University, and Middle East University from Jordan, as well as University of Saba Region, Amran University, and University of Science & Technology from Yemen. By authors, Jibreel (2023) came first with (27) citations of a two-fold article: Translation Technology & Literary Translation, then AlOtaibi (2024) with (25) citations of a two-fold article: Applications of Translation & Teaching Translation.